Methionine and Tryptophan Play Different Modulatory Roles in the European Seabass (Dicentrarchus labrax) Innate Immune Response and Apoptosis Signaling—An In Vitro Study - Machado, Marina; Serra, Cláudia R.; Oliva-Teles, Aires; Costas, Benjamín (Frontiers in Immunology, 2021)
The range of metabolic pathways that are dependent on a proper supply of specific amino acids (AA) unveils their importance in the support of health. AA play central roles in key pathways vital for immune support and individual AA supplementation has shown to be able to modulate fish immunity. In vitro trials are important tools to evaluate the immunomodulatory role of AA, and the present study was conceived to evaluate methionine and tryptophan roles in immune-related mechanisms aiming to understand their effects in leucocyte functioning and AA pathways. For that purpose, head-kidney leucocytes were isolated and a primary cell culture established. The effect of methionine or tryptophan surplus on cell viability was assessed. Medium L-15 10 % FBS without AA addition (0.5mM of L-methionine, 0.1 mM of L-tryptophan) was used as control. To that, L-methionine or L-tryptophan were supplemented at 1 and 2 times (M1x or M2x, and T1x or T2x). Nitric oxide, ATP, total antioxidant capacity, and immune-related genes were evaluated in response to lipopolysaccharides extracted from Photobacterium damselae subsp. piscicida or UV-inactivated bacteria). Moreover, caspase 3 activity and apoptosis-related genes were evaluated in response to the apoptosis-inducing protein, AIP56. Distinct roles in leucocytes' immune response were observed, with contrasting outcomes in the modulation of individual pathways. Methionine surplus improved cell viability, polyamine production, and methionine-related genes expression in response to an inflammatory agent. Also, methionine supplementation lowered signals of apoptosis by AIP56, presenting lower caspase 3 activity and higher il1β and nf-κb expression. Cells cultured in tryptophan supplemented medium presented signals of an attenuated inflammatory response, with decreased ATP and enhanced expression of anti-inflammatory and catabolism-related genes in macrophages. In response to AIP56, leucocytes cultured in a tryptophan-rich medium presented lower resilience to the toxin, higher caspase 3 activity and expression of caspase 8, and lower expression of several genes, including nf-κb and p65. This study showed the ability of methionine surplus to improve leucocytes' response to an inflammatory agent and to lower signals of apoptosis by AIP56 induction, while tryptophan attenuated several cellular signals of the inflammatory response to UV-inactivated bacteria and lowered leucocyte resilience to AIP56.